Most Frequent Physical Symptoms of Premenstrual Syndrome among Reproductive Age Group Women in Rural Area - Lakshmi D; Felix, John William A; Jayasree TM (National Journal of Community Medicine, 2018)
Introduction: Premenstrual syndrome (PMS) is a physical, cogni- tive, affective and behavioural symptoms occuring preceding menstruation and disappears after menstruation. It is reported that 50- 80% of women experience PMS. Studies revealed almost 75% of women belonging to reproductive age group experienced symp- toms associated with menstruation. Objective: This study was done to find out distribution of physi- cal symptoms of premenstrual syndrome among study population and also to assess the most frequent physical symptoms of PMS among study population. Methodology: This descriptive cross sectional study was con- ducted in parangipettai town, Cuddalore district among 650 wom- en of reproductive age. Pretested Proforma was used to collect da- ta. The sampling technique used was single stage area wise cluster sampling technique. Results: Out of 650 women, 519 had atleast any one of the follow- ing the physical symptoms. The ranking reveals that general aches and fatigue are the most frequently reported physical symptoms of PMS. The next symptom will be head ache and back ache. Muscle stiffness and painful breasts ranked as the third group of symp- toms followed by other symptoms. Conclusion: General aches, fatigue, headache and backache are the most frequently occurring physical symptoms.